Trigonometric functions and some trigonometrical identities - Laxmi Rathour; Dragan Obradovic; Shiv Tiwari; Lakshmi Mishra; Vishnu Mishra (Computational Algorithms and Numerical Dimensions)
Trigonometry is a part of mathematics which deals with specific functions of angles and their application, and it is studies of the dependence between the sides and angles of a triangle. The word trigonometry is associated the operations between the sides and angles of the triangles. Initially, it aimed to calculate the values of all elements of a triangle (height, centroid length, bisector, radius, area and angles) using data sufficient to determine the triangle. In the paper, trigonometric functions are defined, and some statements about trigonometric identities are stated and proved.